Lithium ion battery
By setting protective coatings on the positive and negative electrode sheets of lithium-ion batteries and adjusting the structure of the electrode sheet and separator, the problem of poor thermal stability and safety performance of lithium-ion batteries is solved, and higher thermal stability and safety are achieved .
Patent Information
- Application Number
- CN202411386256.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
The thermal stability and safety performance of lithium-ion batteries are poor, which can easily lead to spontaneous ignition and fire accidents.
Protective coatings are provided on the positive electrode sheet and negative electrode sheet of lithium-ion battery, and the thermal insulation and conductivity are improved by adjusting the thickness and bonding strength of the electrode sheet and the membrane to meet specific relationships to prevent heat diffusion and prevent short circuits caused by excessive shrinkage of the diaphragm.
It effectively delays the internal heat diffusion speed of the battery, improves thermal stability and safety performance, reduces the risk of fire and explosion at high temperatures, and extends the safe use time of the battery.
Smart Images

Figure CN119208752A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery preparation, and in particular relates to a lithium ion battery. Background Art
[0002] Lithium-ion batteries are devices that can realize the mutual conversion of electrical energy and chemical energy. With the advancement of science and technology, the demand for high-performance lithium-ion batteries and their application scenarios are also increasing. At present, while lithium-ion batteries are pursuing high energy density, their rate performance is also getting higher and higher, resulting in worse thermal stability and safety performance. Poor thermal stability will lead to dangerous accidents such as spontaneous combustion, so it is necessary to provide a battery that can provide strong thermal stability and safety performance to reduce the probability of dangerous accidents. Summary of the invention
[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art lithium-ion batteries, such as poor thermal stability and safety performance, which lead to spontaneous combustion and fire, thereby providing a lithium-ion battery.
[0004] To this end, the present invention provides the following technical solutions.
[0005] A first aspect of the present invention provides a lithium ion battery, the battery comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet comprising a positive electrode collector and a first protective coating disposed on at least one surface of the positive electrode collector, the first protective coating comprising an inorganic filler, the inorganic filler being coated with a conductive layer; the negative electrode sheet comprising a negative electrode collector; the thickness T of the first protective coating, the thickness M of the positive electrode collector and the thickness Y of the negative electrode collector satisfy the relationship 1;
[0006]
[0007] The T satisfies: 0.5 μm≤T≤5 μm; the M satisfies: M≥3 μm; and the Y satisfies: 3 μm≤Y≤10 μm.
[0008] Optionally, the relationship 1 satisfies 1.7-3.2.
[0009] The thickness M of the positive electrode current collector satisfies: 7 μm≤M≤12 μm; and / or,
[0010] The thickness T of the first protective coating satisfies: 2 μm≤T≤4 μm.
[0011] The material of the conductive layer includes at least one of ATO, FTO, ITO and carbon material; and / or,
[0012] Based on the total mass of the inorganic filler coated with the conductive layer, the mass content of the conductive layer is 2wt%-40wt%, preferably 10wt%-30wt%; and / or,
[0013] The first protective coating layer also includes at least one of a conductive agent and a binder.
[0014] In a lithium-ion battery, the strength A1 of the negative electrode current collector, the strength A2 of the positive electrode current collector, the elongation B1% of the negative electrode current collector, the elongation B2% of the positive electrode current collector, the bonding strength C between the separator and the negative electrode sheet, and the bonding strength D between the separator and the positive electrode sheet satisfy equation 2:
[0015]
[0016] A1 satisfies: 400MPa≤A1≤700MPa; A2 satisfies: 150MPa≤A2≤300MPa; B1 satisfies: 2%≤B1%≤20%; B2 satisfies: 1%≤B2%≤6%; C satisfies: 1N / m≤C≤80N / m; D satisfies: 1N / m≤D≤80N / m.
[0017] Optionally, the relationship 2 satisfies 1.02-4.49.
[0018] A1 satisfies: 450MPa≤A1≤650MPa; A2 satisfies: 200MPa≤A2≤300MPa; B1 satisfies: 8%≤B1%≤16%; B2 satisfies: 2%≤B2%≤4%.
[0019] At least one surface of the negative electrode current collector is also provided with a second protective coating;
[0020] Preferably, the second protective coating is disposed between the negative electrode current collector and the negative electrode active material layer;
[0021] The thickness of the second protective coating is 0.01 μm-3 μm;
[0022] Preferably, the second protective coating is a carbon coating.
[0023] The positive electrode current collector contains a doping element;
[0024] Preferably, the doping element includes at least one of Cu, Fe, Si, Ti and Mn;
[0025] Preferably, the content of the doping element in the positive electrode current collector is not higher than 1000 ppm.
[0026] The diaphragm includes a substrate layer and a coating layer located on at least one surface of the substrate layer, wherein the coating layer includes at least one layer structure of a ceramic layer and a rubber coating layer.
[0027] The thickness of the substrate layer is 3 μm-16 μm, the porosity is 25%-50%, the air permeability is 50s / 100cc-250s / 100cc, and the pore size distribution is 20nm-90nm.
[0028] The technical solution of the present invention has the following advantages:
[0029] 1. The lithium ion battery provided by the present invention comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive current collector and a first protective coating arranged on at least one surface of the positive current collector, wherein the first protective coating is arranged on at least one surface of the positive current collector, has a certain heat insulation effect, and can prevent part of the residual heat from diffusing to other areas inside the battery, and at the same time, there is a certain difference in the internal resistance of the positive current collector and the negative current collector, so that the speed of heat transmission of the positive and negative current collectors is different, and when the thickness T of the first protective coating, the thickness M of the positive current collector and the thickness Y of the negative current collector satisfy the relationship 1, the heat insulation effect and heat resistance performance of the positive and negative electrode sheets are optimized, the heat diffusion speed inside the battery and the time for the overall temperature of the battery to rise are delayed, the thermal stability of the battery is improved, and there is a longer safety time at high temperature.
[0030] 2. For the lithium-ion battery provided by the present invention, when the strength of the negative electrode collector, the strength of the positive electrode collector, the elongation of the negative electrode collector, the elongation of the positive electrode collector, the bonding strength between the diaphragm and the negative electrode sheet, and the bonding strength between the diaphragm and the positive electrode sheet satisfy the relationship 2, the diaphragm begins to shrink under high temperature conditions. However, since the diaphragm and the positive and negative electrode sheets have a certain bonding strength and are bonded to each other, and the positive and negative electrode collectors have high strengths, they can resist the shrinkage deformation from the diaphragm, avoid direct contact between the positive and negative electrode sheets due to excessive thermal shrinkage of the diaphragm, cause internal short circuit of the battery, and then cause fire, further improving the thermal stability and safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 It is a structural schematic diagram of the negative electrode sheet of the present invention;
[0033] Figure 2 It is a structural schematic diagram of the positive electrode sheet of the present invention;
[0034] Reference numerals:
[0035] 11-negative electrode current collector; 12-second protective coating; 13-negative electrode active material layer;
[0036] 21 - positive electrode current collector; 22 - first protective coating; 23 - positive electrode active material layer. DETAILED DESCRIPTION
[0037] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0038] In the description of the present invention, it should be noted that the terms "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0040] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0041] The present invention provides a lithium-ion battery, in which the positive electrode sheet and the negative electrode sheet have the best heat resistance, can slow down the heat diffusion rate inside the battery, prolong the time for the overall temperature rise of the battery, improve the thermal stability of the battery, and have a longer safety time at high temperatures. The technical solution adopted by the present invention is as follows.
[0042] In a first aspect, the present invention provides a lithium ion battery, the battery comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet comprising a positive electrode collector and a first protective coating disposed on at least one surface of the positive electrode collector, the first protective coating comprising an inorganic filler, the inorganic filler being coated with a conductive layer; the negative electrode sheet comprising a negative electrode collector; the thickness T of the first protective coating, the thickness M of the positive electrode collector and the thickness Y of the negative electrode collector satisfy the relationship 1;
[0043]
[0044] The T satisfies: 0.5 μm≤T≤5 μm; the M satisfies: M≥3 μm; and the Y satisfies: 3 μm≤Y≤10 μm.
[0045] It is understood by those skilled in the art that heat is generated inside the battery during high-rate charge and discharge. Although most of the heat will volatilize, a small amount of heat will still accumulate. When the accumulated heat reaches a certain level, some substances in the battery will produce side reactions, causing the battery to catch fire and cause safety accidents. After a battery with high thermal stability absorbs external heat and generates heat internally, the battery's own heat transfer rate will become lower, delaying the rise in battery temperature and slowing down the side reactions of some substances in the battery. It can work normally at higher temperatures, reduce accidents such as battery fires, and improve safety. In order to solve the problem of thermal stability of the battery, at least one surface of the positive electrode collector of the present invention is provided with a first protective coating, the components of the first protective coating include inorganic fillers, and the inorganic fillers are coated with a conductive layer. The protective coating has a certain heat insulation effect, which can prevent part of the residual heat from diffusing to other areas inside the battery. At the same time, there is a certain difference in the internal resistance of the positive electrode collector and the negative electrode collector, which makes the heat transfer speed of the positive and negative electrode collectors different. When the thickness T of the first protective coating, the thickness M of the positive electrode collector and the thickness Y of the negative electrode collector satisfy the relationship 1, the thermal insulation effect and heat resistance performance of the positive and negative electrode sheets are optimized, which can delay the heat diffusion speed inside the battery and the time for the overall temperature of the battery to rise, thereby improving the thermal stability of the battery and having a longer safety time at high temperatures. It should also be noted that when the thickness T of the first protective coating, the thickness M of the positive electrode collector, and the thickness Y of the negative electrode collector are calculated according to the relationship 1 to exceed 3.93, although heat transfer can be hindered, the amount of active material that can be carried on the electrode will be reduced, causing a significant decrease in the volume energy density. The thickness of the first protective coating is too thick, which increases the internal resistance and deteriorates the battery cycle performance. When it is calculated according to the relationship 1 and is lower than 0.6, although the internal resistance can be guaranteed, the heat resistance is reduced, and it is easily affected by the accumulation of internal and external heat, causing the battery to heat up quickly, the electrolyte decomposes to produce side reactions, and there are problems such as bloating and explosion; the first protective coating is too thin and has no effect, and the first protective coating is too thick, which will cause the current path to be extended, thereby reducing the conductivity and affecting the battery's charge and discharge efficiency.
[0046] The applicant found that the thickness T of the first protective coating satisfies: 0.5μm≤T≤5μm, and the inorganic filler in the first protective coating is coated with a conductive layer, which can make the positive electrode plate have a certain heat insulation effect and hinder the diffusion of some residual heat; the positive electrode plate is provided with the first protective coating, and the transfer rate of heat generated outside and inside the battery is reduced, which will not cause the overall temperature of the battery to rise rapidly, and avoid the occurrence of side reactions of some substances, and then bloating, rupture, and safety accidents. The thickness M of the positive electrode collector satisfies: M≥3μm; the thickness Y of the negative electrode collector satisfies: 3μm≤Y≤10μm, the thickness of the positive and negative electrode collectors is different, so that their internal resistance is different, and the speed of heat transfer of the positive and negative electrode collectors is different, so that the thermal resistance of the battery is optimized, delaying the internal heat diffusion and temperature rise of the battery, thereby improving the thermal stability of the battery, and the use time at high temperature is longer and the safety is higher. As an example, the thickness T of the first protective coating is 0.5μm, 1.0μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm or in the range formed by any two of the above values; the thickness M of the positive electrode collector is 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm or in the range formed by any two of the above values; the thickness Y of the negative electrode collector is 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm or in the range formed by any two of the above values. The applicant has found that when the thickness M of the positive electrode current collector satisfies: 7 μm≤M≤12 μm, and the thickness T of the first protective coating satisfies: 2 μm≤T≤4 μm, the thermal stability of the battery is optimal.
[0047] In an optional embodiment, the surface density of the negative electrode current collector is not less than 26 mg / m 2 As an example, the surface density of the negative electrode current collector is 26 mg / m 2 , 27mg / m 2 , 28mg / m 2 , 29mg / m 2 , 30mg / m 2 , 31mg / m 2 , 32mg / m 2 , 33mg / m 2 , 34mg / m 2 , 40mg / m 2 , 45mg / m 2 , 50mg / m 2 , 55mg / m 2 , 60mg / m 2, 70mg / m 2 , 80mg / m 2 , 90mg / m 2 Or within the range of any two of the above values. It is understandable that the surface density of the negative electrode current collector will affect the thickness of the negative electrode current collector, and the two are mutually determined. The surface density of the negative electrode current collector meets the requirement of not less than 26 mg / m 2 , so that it can have a relatively suitable thickness. It is well known to those skilled in the art that the negative electrode current collector can be copper foil, nickel foil, iron-nickel alloy foil, copper-nickel alloy foil, etc. As a preferred embodiment, the thickness of the negative electrode current collector is 3 to 10 μm, and the surface density is 26 to 90 mg / m 2 .
[0048] In an optional embodiment, the surface density of the positive electrode current collector is not less than 18 mg / m 2 As an example, the surface density of the positive electrode current collector is 18 mg / m 2 , 20mg / m 2 , 22mg / m 2 , 24mg / m 2 , 26mg / m 2 , 27mg / m 2 , 28mg / m 2 , 29mg / m 2 , 30mg / m 2 , 31mg / m 2 , 32mg / m 2 , 33mg / m 2 , 34mg / m 2 Or within the range of any two of the above values. It is understandable that the surface density of the positive electrode current collector will affect the thickness of the positive electrode current collector. The surface density of the positive electrode current collector is not less than 26 mg / m 2 , which can make it have a more suitable thickness. It is well known to those skilled in the art that the positive electrode current collector is aluminum foil, titanium foil, etc. As a preferred embodiment, the thickness of the positive electrode current collector is preferably 7 to 12 μm, and the surface density is 18 to 33 mg / m 2 .
[0049] It should be noted that the surface density of the negative electrode current collector and the positive electrode current collector is obtained by testing according to a method known in the art. For example, a punching machine with a punching diameter of 12 mm / 16 mm is used to punch out small discs of the current collector without any material, and the discs are weighed and the weight m is recorded; the area of the punched disc is calculated according to the diameter of the small disc, and the disc area s is recorded; the surface density of the current collector is obtained using m / s. It can also be understood that the surface density of the current collector is the mass per unit area of the current collector.
[0050] In an optional embodiment, the material of the conductive layer includes at least one of ATO, FTO, ITO and carbon material; wherein ATO is tin dioxide doped with antimony, FTO is tin dioxide doped with fluorine, and ITO is indium oxide doped with tin; the doping amount of antimony in ATO is ≤30%, the doping amount of fluorine in FTO is ≤10%, and the doping amount of tin in ITO is ≤30%. It can be understood that the above conductive layer materials have a good coating effect on inorganic fillers, forming a conductive layer on the outer surface of the inorganic filler, reducing the heat propagation speed and improving the battery safety performance.
[0051] In an optional embodiment, based on the total mass of the inorganic filler coated with the conductive layer, the mass content of the conductive layer is 2wt%-40wt%, preferably 10wt%-30wt%. The present invention coats the inorganic filler with a conductive layer of a specific content, which can improve the conductivity of the first protective coating, so that the battery can take into account both safety performance and cycle performance under high temperature conditions. As an example, based on the inorganic filler coated with the conductive layer, the mass content of the conductive layer is 2wt%, 6wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or within the range of any two of the above values.
[0052] In an optional embodiment, the surface density of the first protective coating is 0.1 mg / cm 2 -1.5mg / cm 2 , preferably 0.5 mg / cm 2 -1.2mg / cm 2 As an example, the surface density of the first protective coating is 0.1 mg / cm 2 , 0.3mg / cm 2 , 0.6mg / cm 2 , 0.9mg / cm 2 , 1.2mg / cm 2 , 1.5mg / cm 2 Or within the range formed by any two of the above values. It is understandable that the surface density of the first protective coating will affect the thickness of the first protective coating. The surface density of the first protective coating is 0.1 mg / cm 2 -1.5mg / cm 2 The thickness of the first protective coating layer may satisfy 0.5 μm ≤ T ≤ 5 μm.
[0053] In an optional embodiment, the surface resistance of the first protective coating is 1mΩ-1000mΩ, preferably 1mΩ-100mΩ. As an example, the surface resistance of the first protective coating is 1mΩ, 5mΩ, 10mΩ, 15mΩ, 20mΩ, 30mΩ, 40mΩ, 50mΩ, 60mΩ, 70mΩ, 80mΩ, 90mΩ, 100mΩ, 200mΩ, 300mΩ, 400mΩ, 500mΩ, 600mΩ, 700mΩ, 800mΩ, 900mΩ, 1000mΩ or in the range of any two of the above values.
[0054] It should be noted that the surface resistance of the first protective coating is obtained by testing according to a method known in the art. Here is a test method: two probes are respectively contacted with the membrane to ensure good contact; then current is applied to the probes to measure the voltage drop of the probes, and according to Ohm's law, the resistance is calculated by the voltage drop and the current value.
[0055] In an optional embodiment, the peel strength between the first protective coating and the positive electrode current collector is 20N / m-1000N / m, preferably 100N / m-500N / m. As an example, the peel strength between the first protective coating and the positive electrode current collector is 20N / m, 50N / m, 80N / m, 110N / m, 140N / m, 170N / m, 200N / m, 230N / m, 260N / m, 290N / m, 320N / m, 350N / m, 380N / m, 410N / m, 440N / m, 470N / m, 500N / m, 600N / m, 700N / m, 800N / m, 900N / m, 1000N / m or in the range of any two of the above values.
[0056] It should be noted that the peel strength is obtained by testing according to a method known in the art. For example, a positive electrode current collector coated with a first protective coating and having a length of 100 mm and a width of 15 mm is cut as a sample to be tested; the positive electrode current collector is fixed to the upper and lower fixtures of a universal tensile machine; the sample is peeled off at 180°, the test speed is 100 mm / min, and the test displacement distance is 80 mm. The peel strength is obtained by converting the parameters measured by the tensile machine.
[0057] In an optional embodiment, the first protective coating further comprises at least one of a conductive agent and a binder; preferably, the mass ratio of the inorganic filler, the conductive agent and the binder in the first protective coating is (60-98):(0-5):(2-4). It should be noted that the conductive agent ratio of 0 refers to the technical solution that the first protective coating does not contain a conductive agent.
[0058] For those skilled in the art, the conductive agent is a common raw material in the art, for example, including one or more of conductive carbon black (SP), acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, metal powder and carbon fiber. The binder is a common raw material in the art, for example, the binder includes an aqueous binder and / or an oil-based binder. The aqueous binder includes one or more of polyacrylic acid (PAA), polyacrylate, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylonitrile (PAN). The oil-based binder includes one or more of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), polyolefins (such as copolymers or homopolymers such as ethylene and propylene), fluorinated rubber, polyimide (PI) and perfluorosulfonic acid ionomer (Nafion).
[0059] In an optional embodiment, the resistivity of the inorganic filler is 1Ω·cm-100Ω·cm, which can improve the thermal resistance coefficient. As an example, the resistivity of the inorganic filler is 1Ω·cm, 3Ω·cm, 5Ω·cm, 7Ω·cm, 9Ω·cm, 10Ω·cm, or within the range of any two of the above values.
[0060] It should be noted that the resistivity of the inorganic filler is measured and obtained according to a method known in the art.
[0061] In an optional embodiment, the average particle size of the inorganic filler is 0.05μm-5μm, preferably 100nm-600nm. It is understandable that after the negative electrode active material is lithiated (lithium-embedded negative electrode active material), the thermal stability will be worse; the particle size of the inorganic particles in the first protective coating is limited to the above range, so that the first protective coating can be made thinner, thereby reducing the energy density loss and taking into account safety. As an example, the average particle size of the inorganic filler is 0.05μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm or within the range composed of any two of the above values.
[0062] In an optional embodiment, the inorganic filler includes at least one of aluminum oxide, magnesium oxide, titanium oxide, zinc oxide, silicon oxide, boehmite, cobalt oxide, iron phosphate, lithium iron phosphate, lithium nickel cobalt manganese oxide and lithium iron manganese phosphate. It is understandable that the above inorganic fillers can improve thermal resistance, reduce the heat transfer rate, and have a certain degree of overheating protection for the battery; and the inorganic filler has the characteristics of high mechanical strength, good stability and good heat resistance. In the case of mechanical abuse of the battery (such as needle puncture, extrusion), the inorganic filler can protect the positive electrode collector well, making it not easy to be exposed, thereby reducing the short circuit probability between the positive electrode collector and the negative electrode active layer, and improving the safety performance and thermal stability of the battery.
[0063] In an optional embodiment, the first protective coating on at least one surface of the positive electrode current collector is a one-layer or multi-layer structure; when the first protective coating is a multi-layer structure, the composition of each coating layer may be the same or different. As an example, the first protective coating is a single-layer structure, a two-layer structure, a three-layer structure, etc.; when the first protective coating is a multi-layer structure, its preparation method is a common method in the art, such as forming a multi-layer structure by multiple coatings.
[0064] It should be noted that a first protective coating may be provided on another surface of the positive electrode current collector. It is understood that the thickness of the first protective coating refers to the thickness of the coating on the same side of the positive electrode current collector.
[0065] In an optional embodiment, the battery further comprises a separator; the strength A1 of the negative electrode current collector, the strength A2 of the positive electrode current collector, the elongation B1% of the negative electrode current collector, the elongation B2% of the positive electrode current collector, the bonding strength C between the separator and the negative electrode sheet, and the bonding strength D between the separator and the positive electrode sheet satisfy equation 2:
[0066]
[0067] A1 satisfies: 400MPa≤A1≤700MPa; A2 satisfies: 150MPa≤A2≤300MPa; B1 satisfies: 2%≤B1%≤20%; B2 satisfies: 1%≤B2%≤6%; C satisfies: 1N / m≤C≤80N / m; D satisfies: 1N / m≤D≤80N / m.
[0068] It is understandable to those skilled in the art that due to the nature of the diaphragm itself, when the battery is heated and its internal temperature reaches a certain value, the diaphragm will shrink thermally. If the diaphragm has a high thermal shrinkage rate, the fully charged positive electrode and negative electrode will be in direct contact, and the battery will short-circuit and catch fire, which will greatly affect safe use. In order to reduce the deterioration of the safety performance of the battery at high temperatures due to the thermal shrinkage of the diaphragm, the applicant has found that the thermal shrinkage rate of the diaphragm is related to the strength and elongation of the positive current collector, the strength and elongation of the negative current collector, and the bonding strength between the diaphragm and the positive and negative electrode sheets. When the strength of the negative electrode collector, the strength of the positive electrode collector, the elongation of the negative electrode collector, the elongation of the positive electrode collector, the bonding strength between the diaphragm and the negative electrode sheet, and the bonding strength between the diaphragm and the positive electrode sheet satisfy equation 2, the battery begins to shrink under high temperature conditions. However, since the diaphragm and the positive and negative electrode sheets have a certain bonding strength and are bonded to each other, the sheets support the diaphragm and inhibit deformation of the diaphragm. At the same time, the positive and negative electrode collectors have high strength and can resist shrinkage deformation from the diaphragm, avoiding direct contact between the positive and negative electrode sheets due to excessive thermal shrinkage of the diaphragm, resulting in internal short circuits in the battery, and further causing fires, further improving the thermal stability and safety performance of the battery. It is also understandable that, when the value calculated according to equation 2 exceeds 5.5 or is lower than 1.01, the diaphragm shrinks due to heat. Since the bonding strength between the diaphragm and the positive electrode sheet or the negative electrode sheet is not strong enough, the positive and negative electrode sheets cannot support the diaphragm and suppress shrinkage. When the diaphragm shrinks to a certain extent, the positive and negative electrode sheets are in direct contact, the entire battery short-circuited, and caused fire, explosion, etc.
[0069] The applicant has found that the strength A1 of the negative current collector satisfies: 400MPa≤A1≤700MPa, the strength A2 of the positive current collector satisfies: 150MPa≤A2≤300MPa, the elongation B1 of the negative current collector satisfies: 2%≤B1%≤20%, and the elongation B2 of the positive current collector satisfies: 1%≤B2%≤6%, which can make the positive and negative current collectors resist the shrinkage deformation caused by the heating of the diaphragm and avoid direct contact between the positive and negative pole pieces due to excessive thermal shrinkage of the diaphragm; the bonding strength C between the diaphragm and the negative pole piece satisfies: 1N / m≤C≤80N / m, and the bonding strength D between the diaphragm and the positive pole piece satisfies: 1N / m≤D≤80N / m, which can make the bonding between the positive and negative pole pieces better.
[0070] As an example, the strength A1 of the negative electrode current collector is 450 MPa, 480 MPa, 510 MPa, 540 MPa, 570 MPa, 600 MPa, 640 MPa, 650 MPa or within a range formed by any two of the above values.
[0071] As an example, the strength A2 of the positive electrode current collector is 200 MPa, 220 MPa, 240 MPa, 260 MPa, 280 MPa, 300 MPa or within a range formed by any two of the above values.
[0072] As an example, the elongation B1% of the negative electrode current collector is 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16% or within the range of any two of the above values.
[0073] As an example, the elongation B2% of the positive electrode current collector is 2%, 2.5%, 3%, 3.5%, 4% or within a range formed by any two of the above values.
[0074] As an example, the bonding strength C between the separator and the negative electrode plate is 1 N / m, 5 N / m, 10 N / m, 15 N / m, 20 N / m, 25 N / m, 30 N / m, 35 N / m, 40 N / m, 45 N / m, 50 N / m, 55 N / m, 60 N / m, 65 N / m, 70 N / m, 75 N / m, 80 N / m or within the range of any two of the above values.
[0075] As an example, the bonding strength D between the diaphragm and the positive electrode plate is 1 N / m, 5 N / m, 10 N / m, 15 N / m, 20 N / m, 25 N / m, 30 N / m, 35 N / m, 40 N / m, 45 N / m, 50 N / m, 55 N / m, 60 N / m, 65 N / m, 70 N / m, 75 N / m, 80 N / m or within the range of any two of the above values.
[0076] The applicant's research found that when A1 satisfies: 450MPa≤A1≤650MPa; A2 satisfies: 200MPa≤A2≤300MPa; B1 satisfies: 8%≤B1%≤16%; and B2 satisfies: 2%≤B2%≤4%, the separator in the battery is bonded to the positive and negative electrode sheets, and the positive and negative current collectors are best able to resist the shrinkage deformation caused by the heat of the separator.
[0077] It should be noted that the strength of the negative current collector, the strength of the positive current collector, the elongation of the negative current collector, the elongation of the positive current collector, the bonding strength between the diaphragm and the negative electrode sheet, and the bonding strength between the diaphragm and the positive electrode sheet are all tested according to methods known in the art, and the results of different test methods are basically the same. List a test method, such as strength and elongation, refer to the GB-228-87 test method, and the test parameters are set to a gauge length of 50mm and a tensile speed of 10mm / min. Test method for the bonding strength between the diaphragm and the electrode sheet: Cut a sample of a 100mm long and 15mm wide current collector and a diaphragm bonded together; fix the diaphragm on the upper and lower fixtures of a universal tensile machine respectively; then peel the sample 180°, the test speed is 100mm / min, the test displacement distance is 80mm, and the bonding strength between the diaphragm and the electrode sheet is obtained through the output data of the tensile machine.
[0078] In an optional embodiment, the strength A1 of the negative electrode current collector is the average value of the tensile strength in the TD and MD directions; preferably, the tensile strength in the TD direction of the negative electrode current collector is not less than 400MPa; preferably, the tensile strength in the MD direction of the negative electrode current collector is not less than 400MPa. As an example, the tensile strength in the TD direction of the negative electrode current collector is 400MPa, 500MPa, 600MPa, 700MPa, or in the range of any two of the above values, preferably 700MPa. The tensile strength in the MD direction of the negative electrode current collector is 400MPa, 500MPa, 600MPa, 700MPa, or in the range of any two of the above values, preferably 700MPa.
[0079] In an optional embodiment, the elongation B1% of the negative electrode current collector is the average of the elongations in the TD and MD directions; preferably, the elongation in the TD direction of the negative electrode current collector is not less than 2%; preferably, the elongation in the MD direction of the negative electrode current collector is not less than 2%. As an example, the elongation in the TD direction of the negative electrode current collector is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or in the range of any two of the above values, preferably not less than 5%. The elongation in the MD direction of the negative electrode current collector is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or in the range of any two of the above values, preferably not less than 5%.
[0080] In an optional embodiment, the strength A2 of the positive current collector is the average value of the tensile strength in the TD and MD directions; preferably, the tensile strength in the TD direction of the positive current collector is not less than 200 MPa; preferably, the tensile strength in the MD direction of the positive current collector is not less than 200 MPa. As an example, the tensile strength in the TD direction of the positive current collector is 200 MPa, 220 MPa, 240 MPa, 260 MPa, 280 MPa, 300 MPa, or in the range of any two of the above values. The tensile strength in the MD direction of the positive current collector is 200 MPa, 220 MPa, 240 MPa, 260 MPa, 280 MPa, 300 MPa, or in the range of any two of the above values.
[0081] In an optional embodiment, the elongation B2% of the positive electrode current collector is the average of the elongations in the TD and MD directions; preferably, the elongation in the TD direction of the positive electrode current collector is not less than 2%; preferably, the elongation in the MD direction of the positive electrode current collector is not less than 2%. As an example, the elongation in the TD direction of the positive electrode current collector is 2%, 3%, 4%, 5%, 6%, or within the range of any two of the above values. The elongation in the MD direction of the positive electrode current collector is 2%, 3%, 4%, 5%, 6%, or within the range of any two of the above values.
[0082] In an optional embodiment, the negative electrode plate includes a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector; the negative active material layer is a one-layer or multi-layer structure, and when the negative active material layer is a multi-layer structure, the composition of each layer may be the same or different. It is understood that the composition of the negative active material layer includes active materials, and the active materials are common raw materials in the art, such as at least one of carbon-based materials, silicon-based materials, tin-based materials, and titanium-based materials; specifically, at least one of artificial graphite, natural graphite, soft carbon, hard carbon, elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon nitrogen composites, silicon alloys, elemental tin, tin oxide compounds, tin alloys, elemental titanium, titanium oxide compounds, and titanium alloys. It is also understood that the composition of the negative active material layer may also include additives, such as conductive agents, binders, and the like. Conductive agents and binders are of known types in the art and are not specifically limited thereto. For example, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, carbon fibers and Ketjen black; the binder includes at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber and polyvinylidene fluoride.
[0083] In an optional embodiment, at least one surface of the negative electrode current collector is also provided with a second protective coating; as a preferred embodiment, the second protective coating is provided between the negative electrode current collector and the negative electrode active material layer; the thickness of the second protective coating is 0.01μm-3μm; the second protective coating is a carbon coating, and the second protective coating is provided in the negative electrode pole piece to improve the conductivity, rate performance and charge and discharge performance. As an example, the thickness of the second protective coating is 0.01μm, 0.1μm, 0.5μm, 1.0μm, 1.5μm, 2μm, 2.5μm, 3μm or within the range of any two of the above values. It is understood that the thickness of the second protective coating is the thickness of the coating on the same side of the current collector. It should be noted that the second protective coating is a one-layer or multi-layer structure. It can also be understood that the components of the second protective coating include carbon materials and may also include components such as binders.
[0084] As a preferred embodiment, Figure 1 As shown, the negative electrode plate includes a negative electrode current collector 11 and a second protective coating 12 arranged on both sides of the negative electrode current collector, and a negative electrode active material layer 13 is arranged on the surface of the second protective coating.
[0085] In an optional embodiment, the negative electrode current collector contains a doping element; the doping element includes at least one of Si, Cr, Mu, Fe, Mg, Mn, Sb, Sn, Ti and Zn. The doping element in the current collector can improve the strength and elongation of the material. Doping Cr, Ti and Zn in the negative electrode current collector can improve the corrosion resistance of the current collector to the electrolyte.
[0086] In an optional embodiment, the content of the doping element in the negative electrode current collector is not higher than 1000 ppm.
[0087] In an optional embodiment, the negative electrode current collector is provided with a groove; the depth of the groove is not higher than the thickness of the negative electrode current collector; the diameter of the groove is not higher than 100 μm; the spacing between adjacent grooves is 0.05 mm-0.5 mm. The negative electrode current collector is provided with a groove to increase the electrolyte wettability of the negative electrode, prevent lithium deposition on the surface of the negative electrode, prevent lithium dendrites from piercing the diaphragm, further prevent the positive and negative electrode plates from directly contacting each other to cause a short circuit in the battery, improve the safety performance of the battery under high temperature conditions, and improve high temperature cycle performance.
[0088] In an optional embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, the positive electrode current collector contains a doping element; the doping element includes at least one of Cu, Fe, Si, Ti and Mn; the content of the doping element in the positive electrode current collector is not higher than 1000ppm. The inclusion of doping elements in the positive electrode current collector can improve the strength and elongation of the positive electrode current collector, enhance toughness, and reduce safety issues caused by curling of the electrode sheet due to overheating inside the battery.
[0089] It is understandable that the composition of the positive electrode active material layer includes positive electrode active material, which is a common raw material in the art, such as lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganate, lithium iron manganese phosphate or lithium titanate. The composition of the positive electrode active material layer also includes auxiliary agents, such as binders, conductive agents, etc., and the binders and conductive agents are made of common raw materials in the art. The conductive agent includes at least one of conductive carbon black, carbon nanotubes, etc.; the binder includes at least one of PVDF, HSV, PTFE, SBR, PAA, etc. Among them, the mass ratio of the positive electrode active material, the conductive agent and the binder is a material known in the art, such as 98:1.5:0.5.
[0090] In an optional embodiment, the first protective coating is disposed between the positive electrode current collector and the positive electrode active material layer. It is understood that the thickness of the first protective coating refers to the thickness of the coating located between the positive electrode current collector and the positive electrode active material layer.
[0091] As a preferred embodiment, Figure 2 As shown, the positive electrode plate includes a positive electrode current collector 21 and a first protective coating 22 arranged on both sides of the positive electrode current collector, and a positive electrode active material layer 23 is arranged on the surface of the first protective coating.
[0092] In an optional embodiment, the elongation at break of the diaphragm in the TD direction is higher than 30%, and the elongation at break in the MD direction is higher than 30%; the tensile strength of the diaphragm in the TD direction is 1200 kgf / cm 2 -7000kgf / cm 2 , the tensile strength in the MD direction is 1200kgf / cm 2 -7000kgf / cm 2 The thermal shrinkage of the diaphragm in the TD direction (105℃1h) is less than 10%, and the thermal shrinkage in the MD direction (105℃1h) is less than 10%; the puncture strength of the diaphragm is greater than 120gf; the friction coefficient is 0.2-0.7; the membrane rupture temperature is greater than 150℃; the closed cell temperature is less than 147℃; the porosity is 38%-68%; and the air permeability is 80-400s / 100cc.
[0093] It should be noted that the elongation at break, tensile strength, thermal shrinkage, puncture strength, friction coefficient, film breaking temperature, closed-cell temperature, porosity, air permeability, etc. of the diaphragm are tested and obtained according to methods known in the art. Here, a test method is listed separately, but not limited to the following method. The elongation at break and tensile strength are carried out in accordance with the provisions of GB / T1040.3-2006, using a sample with a width of (15±0.1) mm, an initial distance between the clamps of the tensile testing machine of (100±5) mm, and a test speed of (250±10) mm / min. The elongation at break and tensile strength of the diaphragm are measured by a tensile machine.
[0094] Thermal shrinkage: First, the diaphragm sample to be cut is flatly clamped in A4 paper, and placed in a punching mold to punch into a size of 100×100mm; secondly, the length is measured using a 2.5D microscope, and the horizontal and vertical lengths are recorded; then the diaphragm sample clamped in A4 paper is placed in an oven and baked at 105℃ for 1h. After cooling for 10min after baking, the diaphragm is immediately measured with a microscope and the thermal shrinkage rate is calculated; the calculation formula for the diaphragm shrinkage rate is:
[0095] Transverse direction (TD) = (width before baking - width after baking) / width before baking × 100%
[0096] Machine direction (MD) = (length before baking - length after baking) / length before baking × 100%.
[0097] Porosity: First, stack the diaphragm into 6 layers, flatten it, and press it tightly to remove the air in the diaphragm. Cut the stacked diaphragm according to the cutting board, and measure the cut sample to be tested to obtain the sample area S. Then measure the thickness of the sample 10 times and calculate the average value B. Use an electronic balance to measure the weight of the diaphragm 3 times and obtain the average value M.
[0098] The porosity of the membrane was calculated according to the following formula:
[0099] Porosity C (%) = [(density of diaphragm raw material×S×B-M) ÷ (density of diaphragm raw material×S×B)]×100%.
[0100] Puncture strength: First, install the required sensors and fixtures on the testing machine, and install the diaphragm sample with a length and width of ≥80mm×80mm on the fixture; secondly, set the puncture speed to 100mm / min, and automatically stop running after the diaphragm is punctured, and obtain the puncture strength through the testing machine data.
[0101] Air permeability: Use a membrane air permeability tester to test the membrane air permeability.
[0102] Friction coefficient: A dynamic friction coefficient tester is used, and the test method is as follows: cut a current collector with a length of 100 mm and a width of 80 mm, place it on a smooth plane, take a 75mm×75mm diaphragm, fix it on a 65mm×65mm slider, and move the slider forward at a constant speed of 100mm / min. The friction force is measured and then the dynamic friction coefficient is obtained.
[0103] Membrane rupture temperature and closed-cell temperature: First, you need to build a battery for testing, which will be used for subsequent heating and resistance measurement; secondly, place the test battery in a temperature-controlled environment, gradually heating from 30°C to 200°C. During the heating process, you need to record the temperature of the test battery and its corresponding resistance value every 5 seconds. Finally, draw the temperature-resistance curve of the test battery based on the recorded data. By calculating the resistance change at intervals of 5 seconds, when the resistance value increases by more than 50Ω for the first time or the resistance value decreases by more than 50Ω for the first time, the closed-cell temperature and membrane rupture temperature are determined respectively. That is, when the resistance value increases by more than 50Ω for the first time, it is recorded as the closed-cell temperature, and when the resistance value decreases by more than 50Ω for the first time, it is recorded as the membrane rupture temperature.
[0104] In an optional embodiment, the diaphragm includes a substrate layer and a coating located on at least one surface of the substrate layer, and the coating includes at least one layer structure of a ceramic layer and a rubber coating layer.
[0105] In an optional embodiment, the substrate layer has a thickness of 3 μm-16 μm, a porosity of 25%-50%, an air permeability of 50 s / 100 cc-250 s / 100 cc, and a pore size distribution of 20 nm-90 nm. As an example, the thickness of the substrate layer is 3μm, 6μm, 9μm, 12μm, 16μm or within the range of any two of the above values; the porosity is 25%, 30%, 35%, 40%, 45%, 50% or within the range of any two of the above values; the air permeability is 50s / 100cc, 80s / 100cc, 110s / 100cc, 140s / 100cc, 170s / 100cc, 200s / 100cc, 250s / 100cc or within the range of any two of the above values; the pore size distribution is 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or within the range of any two of the above values.
[0106] It should be noted that the material of the substrate layer is selected from raw materials known in the art and is not limited thereto; as an example, the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polyphenylene sulfide, polyimide, polystyrene, polytetrafluoroethylene, polymethyl methacrylate, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, cellulose, etc.
[0107] In an optional embodiment, the ceramic layer is disposed on at least one surface of the substrate layer; the thickness of the ceramic layer is 0.3 μm-4 μm, which refers to the total thickness of the ceramic layer on one side of the substrate layer. As an example, the thickness of the ceramic layer is 0.3 μm, 0.9 μm, 1.5 μm, 2.1 μm, 2.7 μm, 3.3 μm, 4.0 μm, or within a range consisting of any two of the above values. It is understood that the ceramic layer can be a single layer or multiple layers.
[0108] In an optional embodiment, the peel strength between the ceramic layer and the substrate layer is higher than 10 N / m. As an example, the peel strength between the ceramic layer and the substrate layer is 11 N / m, 13 N / m, 15 N / m, 17 N / m, 19 N / m, 21 N / m, 23 N / m, 25 N / m, or within a range formed by any two of the above values.
[0109] In an optional embodiment, the components of the ceramic layer include inorganic particles and a binder, and optionally, the mass ratio of the inorganic particles to the binder is (40-95):(5-60); the inorganic particles include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, magnesium hydroxide, silicon dioxide, tin oxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, cerium dioxide, zirconium titanate, barium titanate and magnesium fluoride; the binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene and polyhexafluoropropylene.
[0110] In an optional embodiment, the adhesive layer is disposed on at least one surface of the substrate layer and / or the ceramic layer. As a preferred embodiment, the adhesive layer is disposed on the outer surface of the ceramic layer.
[0111] In an optional embodiment, the thickness of the adhesive layer is 0.3 μm-6 μm; as an example, the thickness of the adhesive layer is 0.3 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, or within a range formed by any two of the above values. It should be noted that the thickness of the adhesive layer is the thickness on the same side of the substrate layer.
[0112] In an optional embodiment, the peel strength between the adhesive layer and the substrate layer is higher than 10N / m; the peel strength between the adhesive layer and the substrate layer is 11N / m, 13N / m, 15N / m, 17N / m, 19N / m, 21N / m, 23N / m, 25N / m or within a range formed by any two of the above values. It is understood that the peel strength between the adhesive layer and the substrate layer is higher than the peel strength between the ceramic layer and the substrate layer.
[0113] In an optional embodiment, the coating layer is a polymer coating; the polymer is a common compound in the art; for example, the polymer includes a copolymer or homopolymer formed by at least one monomer of acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, butyl acrylate, ethylhexyl acrylate, styrene, α-methylstyrene, vinyltoluene, ethylene, vinyl acetate, acrylonitrile, vinylidene fluoride, hexafluoropropylene, and chlorophthalic anhydride; the polymer can also be at least one of polyetherimide, polyamideimide, polyimide, and a copolymer of vinylidene fluoride and hexafluoropropylene.
[0114] In an optional embodiment, the battery further comprises an electrolyte; the electrolyte comprises an electrolyte salt and a solvent; the electrolyte further comprises an additive. It is understandable that the electrolyte is a common raw material for preparing batteries in the art.
[0115] In an optional embodiment, the electrolyte salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0116] In an optional embodiment, the solvent includes at least one of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0117] In an optional embodiment, the additives include negative electrode surface film-forming additives, positive electrode surface film-forming additives, and positive and negative electrode current collector surface film-forming additives; they may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature or low temperature performance, etc. The negative electrode surface film-forming additives, positive electrode surface film-forming additives, and positive and negative current collector surface film-forming additives are common types in the field. For example, surface film-forming additives include DTD, LiODFB, LiPO2F2, etc. These additives can significantly improve the high voltage, low temperature cycle, rate performance, etc. of the battery by adding a small amount. Specifically, DTD is a SEI film-forming additive with an average addition ratio of about 1%. Its main functions include improving the battery's high temperature cycle, high temperature storage and low temperature discharge performance, reducing battery expansion after high temperature placement, reducing capacity attenuation and internal resistance, inhibiting the initial capacity drop of the battery, increasing the initial discharge capacity, improving the stability of the graphite negative electrode, and improving the battery cycle performance. In addition, other additives such as LiODFB and LiPO2F2 also play an important role in lithium battery electrolytes. They can optimize various properties of the electrolyte, such as conductivity, flame retardancy, overcharge protection, etc. It is understandable that additives are selected according to needs and are not specifically limited.
[0118] Example 1
[0119] This embodiment provides a lithium-ion battery, comprising:
[0120] (1) Positive electrode
[0121] TiO2 conductive particles and binder PVDF are mixed in a mass ratio of 95:5, and solvent NMP is added, and a first protective coating slurry with a solid content of 40% is obtained by stirring; the TiO2 conductive particles are coated with an ATO conductive layer, and the proportion of ATO is 10wt% based on the TiO2 conductive particles coated with ATO, and the average particle size of the TiO2 conductive particles is 0.4μm, and the resistivity is 5Ω·cm. The first protective coating slurry is evenly coated on the surfaces of both sides of the aluminum foil by coating, and the aluminum foil containing the first protective coating is obtained after baking. Among them, the thickness M of the aluminum foil, the strength A2 of the aluminum foil, the elongation B2% of the aluminum foil, and the thickness T of the first protective coating on one side of the aluminum foil are shown in Table 1.
[0122] Positive electrode active material particles of lithium cobalt oxide, conductive agent carbon black and binder polyvinylidene fluoride are mixed in a mass ratio of 98:1.5:0.5, and N-methylpyrrolidone is added to obtain a positive electrode slurry, which is evenly coated on the surface of the first protective coating. After baking and rolling processes, a positive electrode sheet is obtained.
[0123] (2) Negative electrode
[0124] The negative electrode active particles artificial graphite, conductive agent carbon black, and binder sodium carboxymethyl cellulose are mixed in a mass ratio of 97:1:2, and water is added to form a negative electrode slurry, which is coated on both sides of the copper foil, and then baked and rolled to obtain a negative electrode sheet. The thickness Y of the copper foil, the strength A1 of the copper foil, and the elongation B1% of the copper foil are shown in Table 1.
[0125] (3) Electrolyte
[0126] Ethylene carbonate (EC), propylene carbonate (PC), ethyl propionate (EP) and propyl propionate (PP) are mixed in a mass ratio of 15:10:30:35 to obtain a mixed solution; LiPF6, fluoroethylene carbonate, 1,3-propane sultone and lithium difluorooxalate borate are slowly added into the mixed solution, mixed evenly, and an electrolyte is obtained after passing the moisture and free acid tests; wherein, based on the total mass of the electrolyte, the content of LiPF6 is 15wt%, the content of fluoroethylene carbonate is 10wt%, the content of 1,3-propane sultone is 5wt%, and the content of lithium difluorooxalate borate is 1wt%.
[0127] (4) Diaphragm
[0128] 80 parts by mass of boehmite (particle size DV90 = 0.2 μm, DV10 = 0.1 μm) and 20 parts by mass of poly(methyl)acrylate were added to 900 parts by mass of deionized water, and mixed evenly to obtain a mixed slurry 1, which was coated on the first surface of the substrate layer by micro-gravure, and dried to obtain a diaphragm with a ceramic layer. 100 parts by mass of polyvinylidene fluoride were added to 900 parts by mass of NMP, mixed evenly to obtain slurry 2, and slurry 2 was coated on the surface of the ceramic layer and the second surface of the diaphragm substrate by micro-gravure to form a coating layer. In the diaphragm, the substrate layer is a wet PE substrate with a thickness of 5 μm, the thickness of the ceramic layer is 0.5 μm, and the thickness of the single-sided coating layer is 1 μm. The bonding strength C between the diaphragm and the negative electrode sheet and the bonding strength D between the diaphragm and the positive electrode sheet are shown in Table 1.
[0129] (5) Lithium-ion battery
[0130] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in sequence, and a bare cell is obtained after winding; the bare cell is placed in a film shell aluminum plastic film, and the electrolyte is injected into the bare cell, and a lithium-ion battery is obtained after vacuum packaging, static, formation, shaping, and capacity testing processes; wherein, the formation process: 0.1C constant current charging 4% SOC, and then 0.2C constant current charging to 10% SOC. Among them, the thickness T of the first protective coating in the positive electrode sheet, the thickness M of the positive electrode collector, the thickness Y of the negative electrode collector, the strength of the negative electrode collector, the strength of the positive electrode collector, the elongation of the negative electrode collector, the elongation of the positive electrode collector, the bonding strength between the separator and the negative electrode sheet, and the bonding strength between the separator and the positive electrode sheet are shown in Table 1.
[0131] Example 2-16
[0132] Example 2-16 provides a lithium-ion battery, which is basically the same as Example 1, except that: the thickness of the first protective coating in the positive electrode plate, the thickness of the positive electrode collector, the thickness of the negative electrode collector, the strength of the negative electrode collector, the strength of the positive electrode collector, the elongation of the negative electrode collector, the elongation of the positive electrode collector, the bonding strength between the diaphragm and the negative electrode plate, and the bonding strength between the diaphragm and the positive electrode plate are different, see Table 1.
[0133] Comparative Examples 1-4
[0134] Comparative Examples 1-4 provide a lithium-ion battery, which is basically the same as Example 1, except that: the thickness of the first protective coating in the positive electrode plate, the thickness of the positive electrode collector, the thickness of the negative electrode collector, the strength of the negative electrode collector, the strength of the positive electrode collector, the elongation of the negative electrode collector, the elongation of the positive electrode collector, the bonding strength between the diaphragm and the negative electrode plate, and the bonding strength between the diaphragm and the positive electrode plate are different, see Table 1.
[0135] Test Case
[0136] This test example provides the performance of lithium-ion batteries in various embodiments and comparative examples, as follows:
[0137] Oven temperature test: fully charge the battery cell to the upper limit voltage of 4.5V, then place the battery cell in the oven, heat it to the target temperature at a heating rate of 5±2℃ / min, keep it for 60min, and then end the test; the target temperature is 130℃, 132℃, 135℃ or 140℃. After the end, if the battery cell does not catch fire or explode, it will be recorded as passed; if the battery cell temperature continues to rise until it catches fire or explodes, it will be recorded as failed. The results are shown in Table 2. Each test temperature includes 5 parallel experiments, and the number of samples that passed the test is recorded as X / 5, where X is the number of samples that passed.
[0138] Needle puncture test: fully charge the lithium-ion battery, then place it on the test bench of the needle puncture test equipment, and pierce the battery from the middle of the battery with a tungsten steel needle with a diameter of 3mm and a needle tip length of 3.62mm at a speed of 100mm / s. The battery is considered to have passed the test if it does not catch fire or explode. Each example is tested 10 times. The needle puncture pass rate is calculated according to the following formula:
[0139] Needle puncture pass rate = number of passes / number of tests.
[0140] Electrochemical performance test: Place the battery in a constant temperature room at 45°C, discharge the battery at 1C to the lower limit voltage (3.0V), charge the battery at 1.5C to the upper limit voltage (4.5V), and then discharge the battery at 1C to the lower limit voltage. The above charge and discharge operation is a test cycle. Calculate the discharge capacity retention rate of the battery after 800 cycles. The initial discharge capacity is Q1, and the discharge capacity after 800 cycles is Q2. The discharge capacity retention rate is calculated by the following formula.
[0141]
[0142] Table 1 Parameters of each embodiment
[0143]
[0144]
[0145] Table 2 Test results of various embodiments
[0146]
[0147] Combined with the results in Table 2, the thickness T of the first protective coating, the thickness M of the positive current collector and the thickness Y of the negative current collector of the present invention satisfy the relationship 1, so that the thermal insulation effect and heat resistance of the positive and negative electrode sheets are optimized, the internal heat diffusion rate of the battery and the overall temperature rise time of the battery are delayed, and the thermal stability of the battery is improved. The fire and explosion of the battery after being placed at different temperatures for a period of time are significantly reduced, and up to 10 parallel samples can all pass the needle puncture test, and the cycle capacity retention rate is high. In particular, when the thickness T of the first protective coating satisfies: 2μm≤T≤4μm, and the thickness M of the positive current collector satisfies: 7μm≤M≤12μm, the cycle performance stability effect is optimal.
[0148] On the basis of satisfying Relationship 1, the strength A1 of the negative electrode collector, the strength A2 of the positive electrode collector, the elongation B1 of the negative electrode collector, the elongation B2 of the positive electrode collector, the bonding strength C between the diaphragm and the negative electrode sheet, and the bonding strength D between the diaphragm and the positive electrode sheet satisfy Relationship 2, which helps to further improve the thermal stability and safety performance of the battery and reduce phenomena such as fire and explosion.
[0149] In combination with the embodiments and comparative examples, in the present invention, T satisfies: 0.5μm≤T≤5μm; M satisfies: M≥3μm; Y satisfies: 3μm≤Y≤10μm, and relation 1 is satisfied, so that the heat resistance of the positive electrode sheet and the negative electrode sheet is optimized, the heat diffusion rate inside the battery is slowed down, the time for the overall temperature rise of the battery is prolonged, the thermal stability of the battery is improved, and there is a longer safety time at high temperatures.
[0150] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A lithium ion battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet comprises a positive electrode current collector and a first protective coating disposed on at least one surface of the positive electrode current collector, the first protective coating comprises an inorganic filler, and the inorganic filler is coated with a conductive layer; the negative electrode sheet comprises a negative electrode current collector; the thickness T of the first protective coating, the thickness M of the positive electrode current collector and the thickness Y of the negative electrode current collector satisfy the relationship 1; The T satisfies: 0.5 μm≤T≤5 μm; the M satisfies: M≥3 μm; and the Y satisfies: 3 μm≤Y≤10 μm.
2. The lithium-ion battery according to claim 1, characterized in that The thickness M of the positive electrode current collector satisfies: 7 μm≤M≤12 μm; and / or, The thickness T of the first protective coating satisfies: 2 μm≤T≤4 μm.
3. The lithium-ion battery according to claim 1, characterized in that The material of the conductive layer includes at least one of ATO, FTO, ITO and carbon material; and / or, Based on the total mass of the inorganic filler coated with the conductive layer, the mass content of the conductive layer is 2wt%-40wt%, preferably 10wt%-30wt%; and / or, The first protective coating layer also includes at least one of a conductive agent and a binder.
4. The lithium-ion battery according to claim 1, characterized in that: The strength A1 of the negative electrode current collector, the strength A2 of the positive electrode current collector, the elongation B1% of the negative electrode current collector, the elongation B2% of the positive electrode current collector, the bonding strength C between the separator and the negative electrode sheet, and the bonding strength D between the separator and the positive electrode sheet satisfy the relationship 2: A1 satisfies: 400MPa≤A1≤700MPa; A2 satisfies: 150MPa≤A2≤300MPa; B1 satisfies: 2%≤B1%≤20%; B2 satisfies: 1%≤B2%≤6%; C satisfies: 1N / m≤C≤80N / m; D satisfies: 1N / m≤D≤80N / m.
5. The lithium-ion battery according to claim 4, characterized in that: A1 satisfies: 450MPa≤A1≤650MPa; A2 satisfies: 200MPa≤A2≤300MPa; B1 satisfies: 8%≤B1%≤16%; B2 satisfies: 2%≤B2%≤4%.
6. The lithium ion battery according to claim 4 or 5, characterized in that: At least one surface of the negative electrode current collector is also provided with a second protective coating; Preferably, the second protective coating is disposed between the negative electrode current collector and the negative electrode active material layer.
7. The lithium-ion battery according to claim 6, characterized in that: The thickness of the second protective coating is 0.01 μm-3 μm; Preferably, the second protective coating is a carbon coating.
8. The lithium ion battery according to claim 1 or 4, characterized in that: The positive electrode current collector contains a doping element; Preferably, the doping element includes at least one of Cu, Fe, Si, Ti and Mn; Preferably, the content of the doping element in the positive electrode current collector is not higher than 1000 ppm.
9. The lithium-ion battery according to claim 4, characterized in that: The diaphragm comprises a substrate layer and a coating layer located on at least one surface of the substrate layer, wherein the coating layer comprises at least one layer structure of a ceramic layer and a rubber coating layer.
10. The lithium ion battery according to claim 9, characterized in that: The thickness of the substrate layer is 3 μm-16 μm, the porosity is 25%-50%, the air permeability is 50s / 100cc-250s / 100cc, and the pore size distribution is 20nm-90nm.
Citation Information
Patent Citations
Laminated battery
CN106575795A
Lithium ion battery
CN107482166A
Lithium ion battery
CN115360323A
Secondary battery and electronic device
CN117317386A
Battery diaphragm and battery
CN117895185A
Cited By
Battery monomer, battery device and electric device
CN119993980A